2017
DOI: 10.1002/2017jb014777
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Triggering of Mud Volcano Eruptions During the 2016–2017 Central Italy Seismic Sequence

Abstract: On 24 August 2016 a seismic event (Mw 6.0) was the first of the long Central Italy sequence (ongoing at the end of 2017) of medium‐to‐high magnitude earthquakes, with nine Mw ≥5 up to October 2017, and with about 74.000 seismic events registered after 1 year. The largest was the Mw 6.5 30 October 2016 event near Norcia. After the major seismic events, 17 mud volcanoes erupted around Monteleone di Fermo village (Marche region). Mud volcano eruptions generally occurred a few hours to a few days after the main ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The predicted PGVs in the region of the caldera are 0.09 to 0.15 m/s, and assuming a shear modulus of 30 GPa and a shear wave velocity of ~3000 m/s, the peak dynamic stress change would then be ~0.9 to 1.5 MPa (Fig. 4), consistent with estimates from similarly sized earthquakes at similar distances (30).…”
Section: Stress Interactionssupporting
confidence: 73%
“…The predicted PGVs in the region of the caldera are 0.09 to 0.15 m/s, and assuming a shear modulus of 30 GPa and a shear wave velocity of ~3000 m/s, the peak dynamic stress change would then be ~0.9 to 1.5 MPa (Fig. 4), consistent with estimates from similarly sized earthquakes at similar distances (30).…”
Section: Stress Interactionssupporting
confidence: 73%
“…The red star indicates the epicenter of the 30 October 2016 Norcia earthquake. The yellow triangle indicates the mud volcanoes located near Monteleone di Fermo, which erupted shortly after the Norcia earthquake (Maestrelli et al, ).…”
Section: Analysis Of the Postseismic Strain Stylementioning
confidence: 99%
“…Coseismic effect includes remarkable and diffuse surface faulting (e.g., Civico et al, ; Villani et al, ). Moreover, the emplacement of mud volcanoes about 30 km NE of Norcia shortly after the mainshock suggests dynamic stress transfer by seismic waves (Maestrelli et al, ). However, comprehensive analyses of the long‐term and long‐range effects induced by the largest earthquake of the above crisis are not available so far.…”
Section: Introductionmentioning
confidence: 99%
“…This correspondence has been related to the enhanced permeability of the extensional tectonic discontinuities 6 . However, it has been also observed that variations of the volatiles degassing rate are earthquake-related, and are frequently post-seismic [7][8][9] . Thus, fluids geochemistry provides evidences of the episodic large-scale transport of volatiles.…”
mentioning
confidence: 99%